Phytochemicals and antioxidant activities of leaf, node and in vitro-induced callus of Bougainvillea glabra choisy using different solvents - Nasrat, Mohammad Nasim (2022)
Bougainvillea, popularly known as ‘Bunga kertas’ in Malaysia, is thoroughly explored for nutritional and medicinal purposes. Bougainvillea has been shown to possess alkaloids, flavonoids, cardiac glycosides, saponins, and beta-cyanins, which are widely used in folk medicine to treat different illnesses. Despite its major conventional therapeutic importance, only limited attempts have been made to investigate this species' chemical and pharmacological properties in relation to its medicinal uses. Therefore, this study was conducted to determine the effect of in vitro induced callus under different light conditions and plant growth regulators on phytochemical and antioxidant activities using different extraction solvents. In this study, the leaves and nodes were collected and dried in an oven at a temperature of 40 °C for 48 hours until the weight remained constant. The dried materials made into fine powder using mortar and pestle, then different solvents (aqueous, ethanol, acetone, and hexane) were used for extraction purposes. Subsequently, the phytochemicals (total phenolic and total flavonoid contents), and antioxidant activities such as 2,2-diphenyl-1-picrylhydrazyl (DPPH), 2,2’-azinol-bis (3-ethylbenzothiazoline-6-sulfonic acid (ABTS) and iron (II) chelating activity were assayed using a spectrophotometer. For the second experiment, leaves and nodes of the plants were used for in vitro surface sterilization. Different concentrations of Clorox® (10, 20, 30 and 40%) and exposure time (10, 15, and 20 minutes) were applied. For the third experiment, the sterilized nodal segments were used for in vitro callus induction. Different concentrations and combinations of 2,4-D (2.5, 5, and 7.5 μM) and BAP (0.5, 1, and 1.5 μM) were used for callus induction purposes under dark and light conditions. Finally, the phytochemicals screening and antioxidant activities of in vitro-derived calluses and conventional propagated donor plants were measured as per the first experiment to find out and compare the influence of callus induction on secondary metabolite production potential. The results from the first experiment showed that leaf segment extracted with aqueous extract had a significantly superior effect than other plant parts and solvents where it achieved the highest total phenolic content (58.04 mg GAE/g DW), total flavonoid content (127.93 mg RE/g DW), DPPH free radical scavenging (10.08 mg TE/g DW), ABTS scavenging activity (1.59 mg TE/g DW), respectively. Based on the results of the callus induction experiment, the maximum days (18.25) to callus initiation recorded when nodal segment cultured on woody plant medium (WPM) supplemented with 7.5 μM 2,4-D without addition cytokinin under light condition. On the contrary, the minimum days (7) to callus initiation were recorded when nodal treated with 2.5, 5 and 7.5 μM 2,4-D + 1 and 1.5 μM BAP under dark conditions, which showed significant differences between various concentrations and combinations of auxin and cytokinin. This study showed that the dark condition is better for callus induction than light condition.